Currency Culture: Australian Identity and Nationalism in New South Wales before the Gold Rushes. Issue 1 (2nd January 2017) - Jones, Benjamin T.
Abstract : This article examines the white, native-born population of New South Wales, known as 'the currency', between the 1820s and the discovery of gold in the 1850s. While Britishness was the dominant cultural influence before, and after, the gold rushes, the 'currency lads and lasses' often found their identity in opposition to British-born colonists, known as 'the sterling'. This early incarnation of Australian nationalism is significant, it will be argued, as it reveals how quickly indigenous roots were claimed at the expense of Aboriginal Australians. Further, rather than a sense of Australianness within a larger British identity, the currency community held Britishness as part of their larger Australian identity. Drawing on examples of popular culture from the theatre, the press, and the sporting arena, this article explores the nature of this unique community who held Britishness as a secular religion but identified most strongly as white Australians.